2017
DOI: 10.1101/110072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning multiple variable-speed sequences in striatum via cortical tutoring

Abstract: Sparse, sequential patterns of neural activity have been observed in numerous brain areas during timekeeping and motor sequence tasks. Inspired by such observations, we construct a model of the striatum, an all-inhibitory circuit where sequential activity patterns are prominent, addressing the following key challenges: (i) obtaining control over temporal rescaling of the sequence speed, with the ability to generalize to new speeds; (ii) facilitating flexible expression of distinct sequences via selective activ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 100 publications
0
64
0
Order By: Relevance
“…It remains possible that some of the important mechanisms are actually implemented in a very different way. For example, the ramping activity might be a consequence of some biochemical processes that are present at the level of individual neurons or synapses in the biological brain 42,43 , but not explicitly modelled in the recurrent neural network, in which all the elements are simple rate neurons. This process can be imitated in the network by tuning the weights between neurons of canonical circuits that essentially are devoted to implementing a specific biochemical process.…”
Section: The Importance Of Ramping Activitymentioning
confidence: 99%
“…It remains possible that some of the important mechanisms are actually implemented in a very different way. For example, the ramping activity might be a consequence of some biochemical processes that are present at the level of individual neurons or synapses in the biological brain 42,43 , but not explicitly modelled in the recurrent neural network, in which all the elements are simple rate neurons. This process can be imitated in the network by tuning the weights between neurons of canonical circuits that essentially are devoted to implementing a specific biochemical process.…”
Section: The Importance Of Ramping Activitymentioning
confidence: 99%
“…Our results, showing that behaviorally relevant striatal dynamics are maintained after motor cortex lesions (Figure 4), show that this activity does not require input from motor cortex as is commonly assumed 75,76 . Recent modeling studies have suggested that sequence-associated neural dynamics in DLS could arise from recurrent activity within the striatum itself 77 . Since the striatum is an inhibitory structure, this would require a permissive excitatory drive which, in our motor cortex lesion rats, could be provided by either of its remaining inputs, from the thalamus or somatosensory cortex respectively 50,53 .…”
Section: The Nature Of the Control Signals In The Dlsmentioning
confidence: 99%
“…But how does the DLS integrate into the larger motor network to serve these functions? A recent model of how cortical and thalamic inputs to striatum contribute to generating sequential behaviors suggested that learned sequences could be stored in intrastriatal synapses 106 . Because striatum is mostly an inhibitory structure, generating the requisite dynamics in its output neurons requires excitatory drive, which the DLS can receive from cortical, thalamic, and -for the direct pathway -nigral inputs 5,6,65 .…”
Section: Dls-projecting Thalamic Neurons Are Necessary For Task Execumentioning
confidence: 99%